IDDF2018-ABS-0113 The safety and tolerability of sof/vel/vox for 8 or 12 weeks in >1, 000 patients treated in the polaris-1, polaris-2, polaris-3, and polaris-4 studies: an integrated analysis. (8th June 2018) - Manns, Michael P; Gane, Edward; Willems, Bernard E; Roberts, Stuart K; Flamm, Steven; Bourliere, Marc; Asselah, Tarik; Alric, Laurent; Hyland, Robert H; Stamm, Luisa M; Huang, KC; Brainard, Diana M; et al.
Abstract : Background: The once-daily fixed-dose combination tablet of sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) was evaluated for the treatment of genotype 1–6 HCV infection in four phase 3 studies in patients with and without compensated cirrhosis. This analysis describes the safety of SOF/VEL/VOX across 4 Phase 3 studies. Methods: Treatment-emergent adverse events (AEs) and laboratory abnormalities were assessed in patients who received SOF/VEL/VOX or placebo for 12 weeks (POLARIS-1), SOF/VEL/VOX or SOF/VEL for 12 weeks (POLARIS-4), or SOF/VEL/VOX for 8 weeks or SOF/VEL for 12 weeks (POLARIS-2 and POLARIS-3). SAEs and deaths were followed until post-treatment Week 24. Data were pooled by treatment regimen. Results: 1056 patients were treated with SOF/VEL/VOX for 8 (n=611) or 12 (n=445) weeks, 700 received SOF/VEL for 12 weeks. 38% had compensated cirrhosis, 28% had a BMI≥30 kg/m2, 36% were female, and 12% were ≥65 years old. AEs are presented in the table. Two deaths were reported, one illicit drug overdose and one attributed to hypertension (on post-treatment Day 76), neither were related to treatment. SAEs and discontinuations were more frequent in the placebo group and occurred with similar frequency in the other groups; none were related to study treatment. Headache, fatigue, nausea, and diarrhoea were the most common AEs. Mild diarrhoea and nausea occurred more frequently in the SOF/VEL/VOX groups. Overall, 5.1%–6.6% of patients who received SOF/VEL/VOX or SOF/VEL had Grade 3 or 4 laboratory abnormalities. Among patients receiving VOX, one patient each had a Grade 3 elevation in ALT and bilirubin (table 1). Conclusions: SOF/VEL/VOX for 8 or 12 weeks in the POLARIS studies was well tolerated with a low frequency of Grade 3 or 4 AEs, SAEs, and AEs leading to discontinuation. The frequency of AEs in the SOF/VEL/VOX groups was similar to SOF/VEL and placebo groups, with higher rates of mild diarrhoea and nausea compared to SOF/VEL. References: 1. Time to get control. A review of the care received by patients who had a severe gastrointestinal haemorrhage. NCEPOD 2015. 2. Shaheen AAM, Kaplan GG, Myers RP.Weekend versus weekday admissions and mortality from gastrointestinal haemorrhage caused by peptic ulcer disease. Clinical Gastroenterology and Hepatology2009;7:303–310.